Politikai földrajzi határ a katonaföldrajzban - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2009)
The issue of state borders is a complex problem of modern geography. The complexity lies in the fact that political, historical, economic, social and military geography applies different approaches of the state border as a geographical factor. Military geography usually discusses the question of borders from the point of view of the art of military science. But this approach leads to a one-sided, simplistic evaluation. The result of the geographical aspect of the modern state and the development of today’s military science is the continuous change of the military geography’s view about the state borders. The current approach of art of military science, in accordance with today’s requirements, must be replaced by an integrated approach of geographical security in relation with state borders as well. The author of the study discusses some of the theoretical questions of borders in light of the above mentioned points of view.